2022
DOI: 10.1515/cclm-2022-0268
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care high-sensitivity troponin-I analysis in capillary blood for acute coronary syndrome diagnostics

Abstract: Objectives Patients with acute coronary syndrome (ACS) should be referred promptly to the hospital to reduce mortality and morbidity. Differentiating between low-risk and high-risk patients remains a diagnostic challenge. Point-of-care testing can contribute to earlier disposition decisions for patients excluded from ACS. This study describes the validation of the Atellica® VTLi. Patient-side Immunoassay Analyzer for high-sensitivity troponin point-of-care (POC) analysis. (The Atellica VTLi i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Ses performances analytiques lui permettent d'obtenir les mêmes performances diagnostiques pour un SCA ST-que celles obtenues par un dosage de Tn-hs mesuré en intra laboratoire par des méthodes conventionnelles comme Abbott ou Siemens [15,18]. Quel que soit la matrice utilisée (sang total, plasma ou capillaire), les performances analytiques restent comparables [22].…”
Section: Discussionunclassified
“…Ses performances analytiques lui permettent d'obtenir les mêmes performances diagnostiques pour un SCA ST-que celles obtenues par un dosage de Tn-hs mesuré en intra laboratoire par des méthodes conventionnelles comme Abbott ou Siemens [15,18]. Quel que soit la matrice utilisée (sang total, plasma ou capillaire), les performances analytiques restent comparables [22].…”
Section: Discussionunclassified
“…18 A very pragmatic approach results from the use of Atellica VTLi Patient-side immunoassay analyzer, which showed equivalent results for all types of blood sampled, including capillary blood, which may represent a significant advantage in the ED. 19 According to the currently published data, the best diagnostic performance of high-sensitivity troponin is recorded in patients with low CV risk, in whom the investigators recorded the highest specificity and negative predictive values for coronary artery disease (CAD). 20 The diagnostic accuracy of absolute versus relative changes in Tn values was investigated by Ravanavena et al, who found that absolute increase in cTn may be superior to the relative change of cTn serum values to predict evolution in patients with ACS.…”
Section: Current Methods To Determine Cardiac Troponinmentioning
confidence: 99%
“…This recommendation is based on data suggesting that these algorithms (especially the 0-1 h algorithm) allow to rule in and rule out NSTEMI in the shortest possible time [15]. Furthermore, in the last 5 years, the clinical results of some point-of-care-testing (POCT) methods (i.e., hs-cTnI POCT), with analytical performance equal to hs-cTnI methods, have been developed and evaluated [25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Considering these analytical improvements and clinical evidence [14][15][16][17][18][19][25][26][27][28][29][30][31][32][33][34][35][36], recent documents and guidelines [14][15][16][17]36,37] recommend the use of accelerated diagnostic protocols, based on the use of hs-cTn, in order to reduce the length of stay in the ED and hospital and thus reducing costs related to the management of patients with thoracic pain, ACS, or acute heart failure (AHF).…”
Section: Introductionmentioning
confidence: 99%